Medical therapy versus trabeculectomy in patients with open-angle glaucoma - Motlagh,Behzad Fallahi (2016)
ABSTRACT Purpose: To compare therapeutic outcomes between trabeculectomy and medical therapy in patients with open-angle glaucoma. Methods: In the present retrospective comparative study, the medical charts of 284 patients (eyes) newly diagnosed with open-angle glaucoma who had received conventional medications (n=188) or undergone fornix-based trabeculectomy (n=96) at a teaching eye hospital were reviewed. Results: At a mean follow-up of 6.6 years, post-treatment changes in intraocular pressure (IOP), visual field (VF), best spectacle-corrected visual acuity (BSCVA), and number of required drugs were significantly more favorable in the surgical group (P<0.001 for all comparisons). However, the frequency of clinically desirable IOP (≤21 mmHg) at the endpoint was comparable between the surgical and medical groups (87.2% vs. 82.3%; P=0.26). The rate of conversion to surgical therapy was 34% in the medical group. A greater baseline requirement for anti-glaucoma drugs (two or more) was the only independent predictor of treatment failure in the present study. Conclusions: Although more severe cases naturally receive trabeculectomy, the surgical approach had greater efficacy than conventional medical therapy in patients with open-angle glaucoma. An initial requirement for two or more anti-glaucoma drugs may predict failure of medical therapy.